One-Stage Total Laparoscopic Treatment for Colorectal Cancer With Synchronous Metastasis. Is It Safe and Feasible? - Sena, Giuseppe; Picciariello, Arcangelo; Marino, Fabio; Goglia, Marta; Rocca, Aldo; Meniconi, Roberto L.; Gallo, Gaetano (Frontiers in Surgery, 2021)
Liver is the main target organ for colorectal cancer (CRC) metastases. It is estimated that approximately 25% of CRC patients have synchronous metastases at diagnosis, and about 60% of CRC patients will develop metastases during the follow up. Although several teams have performed simultaneous laparoscopic resections (SLR) of liver and colorectal lesions, the feasibility and safety of this approach is still widely debated and few studies on this topic are present in the Literature. The purpose of this short Literature review is to understand the state of the art of SLR and to clarify the potential benefits and limitations of this approach. Several studies have shown that SLR can be performed safely and with short-term outcomes similarly to the separated procedures. Simultaneous laparoscopic colorectal and hepatic resections combine the advantages of one stage surgery with those of laparoscopic surgery. Several reports compared the short-term outcomes of one stage laparoscopic resection with open resections and showed a similar or inferior amount of blood loss, a similar or lower complication rate, and a significant reduction of hospital stay for laparoscopic surgery respect to open surgery but much longer operating times for the laparoscopic technique. Few retrospective studies compared long term outcomes of laparoscopic one stage surgery with the outcomes of open one stage surgery and did not identify any differences about disease free survival and the overall survival. In conclusion, hepatic and colorectal SLR are a safe and effective approach characterized by less intraoperative blood loss, faster recovery of intestinal function, and shorter length of postoperative hospital stay. Moreover, laparoscopic approach is associated to lower rates of surgical complications without significant differences in the long-term outcomes compared to the open surgery.